INCLUSION OF CHILDREN WITH INTELLECTUAL AND MULTIPLE DISABILITIES: A COMMUNITY-BASED REHABILITATION APPROACH, INDIA (Journal of Special Education and Rehabilitation, 2013)
Background: Inclusion of children with intellectual disabilities (ID) and multiple disabilities (MD) in regular schools in India is extremely poor. One of the key objectives of community-based rehabilitation (CBR) is to include ID & MD children in regular schools. This study attempted to find out association with age, ID severity, poverty, gender, parent education, population, and multiple disabilities comprising one or more disorders cerebral palsy, epilepsy and psychiatric disorders with inclusion among 259 children in Barwani Block of Barwani District in the state of Madhya Pradesh, India.Aim: Inclusion of children with intellectual and multiple disabilities in regular schools through CBR approach in India.Result: Inclusion was possible for borderline 2(66.4%), mild 54(68.3%), moderate 18(18.2%), and age range from 5 to 12 years 63 (43%). Children living in poor families 63 (30.6%), not poor 11(18.9%), parental education none 52 (26%), primary level 11 (65%), middle school 10 (48%) high school 0 (0%) and bachelor degree 1(7%), female 34 (27.9%), male 40 (29.2%), tribal 40 (28.7%), non-tribal 34(28.3%) and multiple disabled with cerebral palsy 1(1.2%), epilepsy 3 (4.8%) and psychiatry disorders 12 (22.6%) were able to receive inclusive education. Significant difference in inclusion among ID categories (c2=99.8, p < 0.001), poverty (c2=3.37, p 0.044), parental education (c2=23.7, p < 0.001), MD CP (c2=43.9, p < 0.001) and epilepsy (c2=22.4, p < 0.001) were seen.Conclusion: Inclusion through CBR is feasible and acceptable in poor rural settings in India. CBR can facilitate inclusion of children with borderline, mild and moderate categories by involving their parents, teachers and community members.
Keywords: Intellectual Disability; Multiple Disability; Inclusion; Intelligence Quotient (IQ); Cerebral Palsy; Epilepsy; Psychiatric Disorders; Community-based Rehabilitation; India